Tissue-resident macrophages: guardians of organ homeostasis. Issue 6 (June 2021) - Nobs, Samuel Philip; Kopf, Manfred
Abstract : Tissue-resident macrophages (MTR ) have recently emerged as a key rheostat capable of regulating the balance between organ health and disease. In most organs, ontogenetically and functionally distinct macrophage subsets fulfill a plethora of functions specific to their tissue environment. In this review, we summarize recent findings regarding the ontogeny and functions of macrophage populations in different mammalian tissues, describing how these cells regulate tissue homeostasis and how they can contribute to inflammation. Furthermore, we highlight new developments concerning certain general principles of tissue macrophage biology, including the importance of metabolism for understanding macrophage activation states and the influence of intrinsic and extrinsic factors on macrophage metabolic control. We also shed light on certain open questions in the field and how answering these might pave the way for tissue-specific therapeutic approaches. Highlights: Virtually every tissue in mice and humans has one or multiple distinct tissue-resident macrophage (MTR ) populations, which are crucial for the maintenance of tissue homeostasis. Dysregulated MTR function can have detrimental consequences in the context of many diseases, including cardiovascular and metabolic pathologies, obesity, cancer, amyloidosis, and infections. MTR in mammals derive from diverse origins, including yolk sac, fetal liver, and bone marrow. This differentiation stems from various embryonic precursor stages as well as bone marrow-derived monocytes. Metabolism can regulate the phenotype of MTR and profoundly impact their function.